Phages for Africa: The potential benefit and challenges of phage therapy for the livestock sector in sub-Saharan Africa - Makumi, Angela; Mhone, Amos L.; Odaba, Josiah; Guantai, Linda; Svitek, Nicholas (MDPI, 2021)
One of the world’s fastest-growing human populations is in Sub-Saharan Africa (SSA), accounting for more than 950 million people, which is approximately 13% of the global population. Livestock farming is vital to SSA as a source of food supply, employment, and income. With this population increase, meeting this demand and the choice for a greater income and dietary options come at a cost and lead to the spread of zoonotic diseases to humans. To control these diseases, farmers have opted to rely heavily on antibiotics more often to prevent disease than for treatment. The constant use of antibiotics causes a selective pressure to build resistant bacteria resulting in the emergence and spread of multi-drug resistant (MDR) organisms in the environment. This necessitates the use of alternatives such as bacteriophages in curbing zoonotic pathogens. This review covers the underlying problems of antibiotic use and resistance associated with livestock farming in SSA, bacteriophages as a suitable alternative, what attributes contribute to making bacteriophages potentially valuable for SSA and recent research on bacteriophages in Africa. Furthermore, other topics discussed include the creation of phage biobanks and the challenges facing this kind of advancement, and the regulatory aspects of phage development in SSA with a focus on Kenya.